2022
DOI: 10.1038/s41598-022-11929-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-intensive care syndrome in mechanically ventilated patients with COVID-19

Abstract: Coronavirus disease 19 (COVID-19) patients usually require long periods of mechanical ventilation and sedation, which added to steroid therapy, favours a predisposition to the development of delirium and subsequent mental health disorders, as well as physical and respiratory sequelae. The aim of this study was to determine the prevalence of post-intensive care syndrome (PICS) at 3 months after hospital discharge, in a cohort of mechanically ventilated patients with severe acute respiratory syndrome coronavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 50 publications
4
27
0
4
Order By: Relevance
“…Nevertheless, our study might even underestimate the incidence of delirium in the ICU, if one considers that some ICU patients were already transferred back to their referral hospitals before being weaned. This needs to be emphasized as other studies have described a higher predisposition to delirium in mechanically ventilated COVID-19 patients [ 24 ].…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, our study might even underestimate the incidence of delirium in the ICU, if one considers that some ICU patients were already transferred back to their referral hospitals before being weaned. This needs to be emphasized as other studies have described a higher predisposition to delirium in mechanically ventilated COVID-19 patients [ 24 ].…”
Section: Discussionmentioning
confidence: 91%
“…In our study, most participants mentioned that it was also a major challenge to provide psychological care and rehabilitation care while completing tasks involving the diagnosis and treatment of elderly patients with severe COVID-19. Previous studies have con rmed that elderly patients with severe illness often have a high level of psychological distress and need for psychological support [30][31][32]. However, the current status of psychological support for critically ill patients is unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified PTSD as a major health issue caused by COVID-19 infection, and survivors after an ICU stay are at higher risk of developing this condition, as compared to the population not exposed to the most severe forms of the disease or managed at home without any ventilatory support [ 17 , 24 , 25 ]. Risk factors related to the development of PTSD after ICU discharge include the length of hospital and ICU stays, mechanical ventilation, disease severity, higher levels of PCR, or lower PaO 2 /FiO 2 ratio [ 18 ].…”
Section: Introductionmentioning
confidence: 99%